A position on some of the views of Sheikh Mohammed Khal in the book (Al-Bitushi). - Mirawi, Prof. Dr. Mohammad Zuber Bayazi; Naqshbandi, L. Lala Sheikh Abdul Rauf (Sulaimani Journal for Humanities, 2023)
Religious schools in Kurdistan, as the main center of education, have educated many talented people since their establishment and operation, and Kurdistan's history in this area is very beautiful. One of the great Kurdish personalities who graduated from traditional schools in Kurdistan is Sheikh Mohammed Khale. Sheikh Mohammed Khal as a bright star in the sky of Kurdistan science and literature, has illuminated many gaps and even crossed the borders and as an influential person and opinion, in the fields of commentary, literature, history, etc., is remarkable. His works are the explanation and reconstruction of Kurdish Islamic literature. Sheikh Khal has been swimming in the bottomless ocean of Islamic and Kurdish science and literature for a long time as a skilled swimmer and has presented many unique works to the society. His interests include reviving the names and works of Kurdish scholars. He has written biographies of Sheikh Ma'roof Node, Mullah Abdullah Betooshi and Mufti Zahawi. In this study, we have tried to weigh the book (Al-Bitushi) Sheikh Khal and open a mind on the unique work that describes the personality of Betushi, his life and works and is a valuable resource that is available to us today. Our research methodology is according to library sources.
Keywords: Mohammed Khal; (AlBitushi); Moral Purposes